Fight for Nothing: Fight Club and Nihilism in Capitalist Society - Karakasis, Georgios; Lavilla de Lera, Jonathan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This paper analyses the movie Fight Club (1999) from the philosophical point of view. We reflect on the split personality of the protagonist, showing how the former represents the subject of the modern society, who, unable to find completion in ceaseless consumerism, embarks upon a personal journey towards the annihilation of every value of his world. This process of annihilation, which at first takes the form of a closed group of people, evolves into an expansive way of annihilation. The latter symbolizes modern society’s evolved subject’s will to destroy the foundations of capitalist society.